All Quiet? The Memory and Historiography of the First World War in Poland - Maciej Maria Górny (Universitat Autònoma de Barcelona, 2014)
The differences of memory cultures between the Europe’s East and West are partly an effect of striking misbalance of historical knowledge about the course of the war and its effects. Although collective memory and historiography are surely not the same, there is a connection between the two. The weakness of the memory in Eastern Europe is at the same time the cause and the effect of the long standing negligence by indigenous historians. The present study examines the interconnections between collective memory and historiography in East Central Europe. One the main characteristics of maneuver warfare on the Eastern and Balkan front that differed most from the Western front had been the constant proximity of military and civilian affairs. Contrary to mostly regular trench warfare, in the East soldiers met their civilian compatriots or the population of the enemy country on a daily basis. Some of the specific modes of contact between civilians and military men belong to the most promising fields of the Eastern Europe’s First World War studies: occupation (of Poland, Lithuania, Latvia, Estonia, Belarus, Ukraine, Serbia and Romania), voluntary and forceful migrations as well as the phenomenon of violence which is inseparable from both aforementioned questions. In this author's view, the position of the First World War depends in the long run on its status within or outside dominating national historical narratives.